Gut bacterial L-lysine alters metabolism and histone methylation to drive dendritic cell tolerance - Qiang Tang; Guangyue Fan; Xianping Peng; Xinyu Sun; Xueting Kong; Lisong Zhang; Chunze Zhang; Yandi Liu; Jianming Yang; Kaiyuan Yu; Chunhui Miao; Zhi Yao; et al. (Cell Reports)
Summary: Dendritic cells (DCs) are responsible for maintaining tolerance to harmless antigens in the gut; however, the mechanism by which bacterial metabolites induce DC tolerance remains to be studied. Here, we observed that gut commensal bacterium-derived L-lysine stimulated the serine, glycine, one-carbon (SGOC) metabolism through the adenosine monophosphate (AMP)-activated protein kinase (AMPK)/acetyl-coenzyme A (AcCoA)-mechanistic target of rapamycin (mTOR) axis in DCs. This activation led to an increase in S-adenosyl methionine (SAM) and disruptor of telomeric silencing 1-like (DOT1L) expression, resulting in enhanced dimethylation on H3 lysine 79 (H3K79me2) enrichment at Tgfb and signal transducers and activator of transcription 3 (Stat3) gene promoters, which promote immune tolerance characteristics in DCs. The lysine-induced DC tolerance in restoring homeostasis was demonstrated using mouse models of immune-inflammatory diseases and phosphoglycerate dehydrogenase (Phgdh) conditional knockout mice. The single-cell RNA sequencing (scRNA-seq) analysis revealed that L-lysine restored homeostasis during inflammatory disorders by switching DCs to a tolerance state in vivo. Moreover, the enzyme by which bacteria effectively produce L-lysine is identified. The study reveals an unknown mechanism for regulating immune homeostasis through the intricate interplay of bacterial L-lysine, SGOC metabolism, histone methylation, and DC tolerance.